2013
DOI: 10.1177/197140091302600104
|View full text |Cite
|
Sign up to set email alerts
|

Small Intracranial Lipomas may be a Frequent Finding on Computed Tomography of the Brain

Abstract: Intracranial lipomas are described as a rare finding. In this small retrospective analysis of 50 cases undergoing brain CT for various reasons small intracranial lipomas where found in nine patients. In contrast to previous reports lipomas may be a frequent finding on CT imaging of the brain. In particular, these small lipomas seem to be incidental findings lacking clinical relevance. Radiologists should be aware of intracranial lipomas to establish proper differential diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…Interestingly, in our sample, only 50% of the lipomas were initially reported. The same discrepancy between quite a common occurrence and the disregard in the literature has been shown also for small intracranial lipomas on brain CTs [ 3 ].…”
Section: Discussionmentioning
confidence: 71%
“…Interestingly, in our sample, only 50% of the lipomas were initially reported. The same discrepancy between quite a common occurrence and the disregard in the literature has been shown also for small intracranial lipomas on brain CTs [ 3 ].…”
Section: Discussionmentioning
confidence: 71%
“…Intracranial lipomas are congenital lesions because of abnormal differentiation of embryological meninx primitiva (subarachnoid space precursor). These lesions are a rare finding with an incidence of 0.08% and 0.46% in autopsy series [3] . In a review of 3000 brain CT scans of head trauma patients, only 3 lipomas were reported in 0.1% of the scans [3] .…”
Section: Discussionmentioning
confidence: 95%
“…These lesions are a rare finding with an incidence of 0.08% and 0.46% in autopsy series [3] . In a review of 3000 brain CT scans of head trauma patients, only 3 lipomas were reported in 0.1% of the scans [3] . Although several theories tried to explain the cause of intracranial lipomas, one favorable theory is the concept of the meninx primitiva (subarachnoid space precursor) [4] .…”
Section: Discussionmentioning
confidence: 95%
“…Most of the intracranial lipomas are asymptomatic and an incidental finding on brain imaging studies for other conditions, but some are associated with congenital malformations, headache, vertigo, and seizures depending on their location [1 , 4 , 5] . Our patient was presented with forehead scalp swelling that he had since birth and he wanted to remove the lesion with surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…They are usually located in the midsagittal region of the brain mostly in the vicinity of the corpus callosum, quadrigeminal cistern, suprasellar cistern, cerebellopontine angle cistern, and Sylvian cistern [2 , 3] . Most of the intracranial lipomas are asymptomatic and incidental findings on brain imaging studies for other conditions, but some are associated with congenital brain malformations, headache, vertigo, and seizure depending on their location [1 , 4 , 5] . Both CT and MRI can be used for the diagnosis of intracranial lipoma.…”
Section: Introductionmentioning
confidence: 99%